The Impact Of Digital Transformation Through Implementing Blockchain Technology On Enhancing The Accounting Profession In Jordan: A Multimethodology Study - Nehad Ibrahim Ineizeh; Obada Jebreen Hussein; Ibrahim Nehad Ineizeh; Murad Ali Ahmad Al-Zaqeba; Mahmoud AbuDiak (The Elite Scientific Forum, 2024)
Non-Indexed Publication